Status and Distribution of Major Invasive Plant Species in the Dehradun Region of the Uttarakhand Himalaya - Mansi Arora; S.N. Ojha; Maneesha Singh (International Journal of Trends in Horticulture, 2026)
Invasive alien plant species are widely recognized as one of the major threats to global biodiversity and ecosystem stability. Their rapid spread and ability to adapt to different environmental conditions allow them to dominate natural habitats and disrupt ecological balance. The present study examines the status and distribution of major invasive plant species in the Dehradun region of Uttarakhand, which is situated in the Himalayan foothills of northern India. Field surveys were carried out in selected locations of the Selaqui (Dhulkot) area to record invasive plant species and evaluate their occurrence in different habitat types. The investigation recorded a total of ten invasive plant species belonging to five different plant families within the study area. Among these species, Lantana camara was notified as the most dominant and widely distributed invasive plant. The majority of invasive species were mainly observed along roadsides, forest margins, agricultural lands, wastelands, and other disturbed environments where ecological disturbance facilitates their growth and spread. The findings suggest that invasive plants strongly compete with native vegetation for essential resources such as nutrients, light, and water, which can ultimately reduce native plant diversity and alter ecosystem structure and functioning. Furthermore, the increasing dominance of invasive species may negatively influence ecological stability and local biodiversity. Therefore, continuous monitoring, ecological assessment, and the implementation of effective management and control strategies are essential to limit their spread and to conserve the natural ecosystems of the Dehradun region, Uttarakhand.
Keywords: Biodiversity; Habitat; Invasive species; Lantana Camara; ecological disturbance